Hypoxia‐induced pulmonary hypertension and chronic lung disease: caveolin‐1 dysfunction an important underlying feature. (1st March 2019) - Huang, Jing; Frid, Maria; Gewitz, Michael H.; Fallon, John T.; Brown, Dale; Krafsur, Greta; Stenmark, Kurt; Mathew, Rajamma
Abstract : Caveolin‐1 (cav‐1) has been shown to play a significant role in the pathogenesis of pulmonary hypertension (PH). In the monocrotaline model of PH, the loss of endothelial cav‐1 as well as reciprocal activation of proliferative and anti‐apoptotic pathways initiate the disease process and facilitate its progression. In order to examine the role of cav‐1 in hypoxia‐induced PH, we exposed rats and neonatal calves to hypobaric hypoxia and obtained hemodynamic data and assessed the expression of cav‐1 and related proteins eNOS, HSP90, PTEN, gp130, PY‐STAT3, β‐catenin, and Glut1 in the lung tissue. Chronic hypoxic exposure in rats (48 h–4 weeks) and calves (2 weeks) did not alter the expression of cav‐1, HSP90, or eNOS. PTEN expression was significantly decreased accompanied by PY‐STAT3 activation and increased expression of gp130, Glut1, and β‐catenin in hypoxic animals. We also examined cav‐1 expression in the lung sections from steers with chronic hypoxic disease (Brisket disease) and from patients with chronic lung disease who underwent lung biopsy for medical reasons. There was no cav‐1 loss in Brisket disease. In chronic lung disease cases, endothelial cav‐1 expression was present, albeit with less intense staining in some cases. In conclusion, hypoxia did not alter the cav‐1 expression in experimental models. The presence of cav‐1, however, did not suppress hypoxia‐induced activation of PY‐STAT3 and β catenin, increased gp130 and Glut1 expression, or prevent the PTEN loss, indicating cav‐1 dysfunction in hypoxia‐induced PH.